Penser éducation au politique et questions environnementales dans la démocratie - Camille Roelens (Éducation et Socialisation, 2022)
This text confronts education to politics with the revelation of environmental issues from the point of view of the political philosophy of education. First, we lay the groundwork for what an epistemology of political education in democracy might be and what the latter then allows in terms of intellectual work (1). Then we try to see how this model can help us thinking of human autonomy in front of environmental issues (2). Then arises the question of the most appropriate places to think about political education in face of these issues. Here the fields of experience, informal education and individual relation to contemporary cultural productions appear as privileged. A brief illustrative study of the approach and work of the Canadian music group Les Cowboys fringants (3) shows how this type of informal educator can play an important role to provide resources and porpositions of influence for human autonomy in dealing with environmental issues within the democratic political framework.